Diseño de un sistema de gestión ambiental para la Unidad Académica de Ciencias Sociales de la Universidad Técnica de Machala - Rugel Torres, Carlos Aldair (2016)
The integrative project has as a stage the Academic Unit of Social Sciences of the Technical University of Machala, within the unit identified problems and needs that are related to the consumption of electricity, water, office supplies and solid waste management. In order to understand the dimension of the identified problems, it was necessary to collect information from the classroom and administrative blocks through the method of observation, interviews and surveys directed at students and administrative staff, through the analysis of the information obtained are proposed Measures that seek to improve administrative management and the degree of environmental impact caused by the activities developed within the educational unit in the environment. The overall objective of the integrative proposal is focused on the design of an environmental management system through which continuous improvement of the processes and activities carried out within the academic unit is taken, as a guide to international regulations ISO 14001 which specifies the requirements for an environmental management system that allows the organization to develop and implement a policy and objectives that take into account legal requirements and information on significant environmental aspects, as specific objectives manifests the need to Control and optimize the consumption of electricity, water and office supplies and the improvement of the system of management and disposal of solid waste in the Academic Unit of Social Sciences.